Pendampingan Pembelajaran Al-Qur’an Melalui Metode Tilawati di Masjid Taqwa Jambak Lubuk Sikaping - Seswi Derti; Martin Kustati; Gusmirawati Gusmirawati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This community service aims to provide assistance in reciting the Qur'an using the tilawati method at the Taqwa Mosque in Lubuk Sikaping. Qur'anic learning at the Taqwa Mosque is not effective, due to the lack of motivation and teaching methods used by the teaching teachers. One of the proposed solutions is to use the tilawati method to increase children's motivation and ability to read the Qur'an. The method used in this community service is PAR (Participatory Action Research), which involves a practical approach and direct assistance. The results of this community service are that the students began to be enthusiastic about learning to read the Qur'an, especially with the introduction of several rhythms of reading the Qur'an, they became addicted to continuing to repeat the recitation of the Qur'anic verses until the rhythm was in accordance with what they had been taught. The teachers and students, in practice, showed good skills and acceptance of the tilawati method in reading the Qur'an. Therefore, based on the results of this community service, it can be seen that the tilawati method can be used as one of the methods in learning the Qur'an at the Taqwa Mosque TPA Jambak Lubuk Sikaping.